Understanding and addressing the 'fit' between user, technology and organization in evaluating user acceptance of healthcare technology - K.-S Mohamadali, Noor Azizah (2012)
In this paper, we discuss the importance of addressing the ‘fit’ between user, technology and organization in evaluating user acceptance of healthcare technology. We give an overview of evaluation dimensions and explore two models that are related to ‘fit’. We demonstrate how users’ acceptance factors in previous studies could be better explained through the perspective of ‘fit’ between user, technology and organization. We believe that the importance of ‘fit’ needs to be understood in greater detail among the evaluation research community. The ‘fit’ between user, technology, and organization needs to be addressed together with the factors that influence user acceptance. This paper attempts to gain empirical support for the inclusion of ‘fit’ between user, technology and organization when evaluating user acceptance of the healthcare technology.